THE ROLE OF THE POLRI IN THE LAW ENFORCEMENT OF THE DISTRIBUTION OF HATE SPEECH IN THE CITY OF BATAM, INDONESIA - Essty Yana; Florianus Yudhi Priyo Amboro; Eko Nurisman; Nur Hadiyati (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2021)
The rise of hate speech cases through social media is the background for the writer in taking the object as research material. The implementation of applicable law must be in accordance with the conditions in daily life and be supported by the role of law enforcement and the community. The understanding of hate speech, the role of the police in law enforcement related hate speech then the solution to the existence of legal constraints is part of the formulation of the problem in this research. This research uses empirical legal research methods, so the basis for the writer to take primary data in the field directly with the first resource person. Supported by the existence of other laws and regulations in analyzing the data that has been obtained. This thesis research was carried out by taking data directly in the field and continued with literature study. Using qualitative data analysis methods as well as content in this thesis research. The results of the research carried out have proceeded in such a way over cases of hate speech that occurred. Interview data, statistical data and decision data are the latest data on hate speech cases. The role of law enforcement has been running in accordance with applicable laws, legal solutions to the existence of law enforcement constraints have been able to be resolved from the law enforcement authorities themselves.